Thermoregulation in the horse at rest and during exercise - Marlin, David (MTT, 2008)
Metabolism results in the production of heat. During exercise the rate of heat production may exceed that at rest by a factor of forty times due to increased metabolic activity within working muscles. As heat production is related to the level of metabolic activity, metabolic heat production is easily estimated from whole body oxygen consumption measurements. As an animal with a high mass specific maximal oxygen uptake, the horse has a high capacity for heat production even when scaled for body mass. For athletic horses the relationship between body mass and body surface area allows heat retention, which is advantageous in cool but disadvantageous in hot climates. Horse s rely primarily on sweating to dissipate heat and possess a sweating capacity unequalled in the animal kingdom with regional rates of up to 50 ml/m2/min and whole body losses of 15 l/h. The horse also has a high capacity for thermotolerance, which it requires when muscle temperatures can reach 48°C and rectal temperatures in excess of 42°C. As part of its ability to tolerate such temperatures the horse does possess some capacity for selective brain cooling. In the last decade and a half, advances in understanding of thermoregulation in the athletic horse were driven by Olympic Games and World Equestrian Games being held in thermally adverse environments. These studied lead to developments in areas such as transport, acclimatisation, competition scheduling, competitive demands, assessment of thermal stress and cooling.
Keywords: Ko; horse; thermoregulation; exercise; heat; cold